Response-dependent contributions of human primary motor cortex and angular gyrus to manual and perceptual sequence learning. - Rosenthal, C; Roche-Kelly, E; Husain, M; Kennard, C (2009)
Motor sequence learning on the serial reaction time task involves the integration of response-, stimulus-, and effector-based information. Human primary motor cortex (M1) and the inferior parietal lobule (IPL) have been identified with supporting the learning of effector-dependent and -independent information, respectively. Current neurocognitive data are, however, exclusively based on learning complex sequence information via perceptual-motor responses. Here, we investigated the effects of continuous theta-burst transcranial magnetic stimulation (cTBS)-induced disruption of M1 and the angular gyrus (AG) of the IPL on learning a probabilistic sequence via sequential perceptual-motor responses (experiment 1) or covert orienting of visuospatial attention (experiment 2). Functional effects on manual sequence learning were evident during 75% of training trials in the cTBS M1 condition, whereas cTBS over the AG resulted in interference confined to a midpoint during the training phase. Posttraining direct (declarative) tests of sequence knowledge revealed that cTBS over M1 modulated the availability of newly acquired sequence knowledge, whereby sequence knowledge was implicit in the cTBS M1 condition but was available to conscious awareness in the cTBS AG and control conditions. In contrast, perceptual sequence learning was abolished in the perceptual cTBS AG condition, whereas learning was intact and available to conscious awareness in the cTBS M1 and control conditions. These results show that the right AG had a critical role in perceptual sequence learning, whereas M1 had a causal role in developing experience-dependent functional attributes relevant to conscious knowledge on manual but not perceptual sequence learning.